Pengembangan Bahan Ajar Modul Terintegrasi Problem Based Learning pada Materi Laju Reaksi - Risdayati Simorangkir; Marudut Sinaga (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to (1) determine the results of the analysis of chemistry teaching materials on the reaction rate material used in schools according to the BSNP standard, (2) describe the feasibility (validity) of the integrated problem based learning module teaching materials on the reaction rate material based on the BSNP criteria (3 ) knowing student learning outcomes have increased after being given teaching materials Integrated Problem Based Learning Module on the reaction rate material, (4) knowing students about teaching materials for integrated problem based learning module on reaction rate materials that have been developed. This research uses the method (R&D) with the ADDIE model covering the stages (analysis, design, development, implementation and evaluation). The product developed was validated by 4 expert validators consisting of 2 chemistry lecturers and 2 chemistry teachers. From the results of hypothesis testing carried out produces tcount > ttable, which is 6.567 > 1.0705618. The assessment of the presentation of the level of student interest in the module that has been developed is 88.33 (very high).